The Development of Euclid Geometry’s Teaching Materials Based on KKNI to Improve Students Cognition Analysis and Deductive Reasoning Abilities - Dwi Antari Wijayanti; Pinta Deniyanti Sampoerno; Qorry Meidianingsih (Urogram Studi Pendidikan Matematika, Universitas IVET, 2021)
This research aims to develop teaching materials that have been produced by the application of the learning model Means Ends Analysis in the form of Classroom Action Research. The development carried out in this study resulted in Euclid Geometry teaching materials based on KKNI to improve cognitive analytical skills and deductive reasoning of students of the Mathematics Education Study Program, State University of Jakarta. There were five steps carried out in developing this teaching material, including initial research, collecting data and information on needs, planning changes to teaching materials, developing early teaching materials, field trials, and revisions. The teaching material developed is suitable for use in Euclid's Geometry learning because it has passed the expert validation process. Also, this teaching material has been tested on students who have been and are currently taking Euclid's Geometry courses. This concludes that Euclid Geometry teaching materials based on KKNI are feasible and can be used as a handbook for students in taking Euclid Geometry courses in the Mathematics Education Study Program of FMIPA UNJ. Keywords: Euclid's geometry, learning models, means-ends analysis, classroom action research.